Ground Improvement By Using Geosynthetics In Slope W - Sukri, Nurin Syazwina (Universiti Sains Malaysia, 2021)
Due to the geography and weather conditions in Malaysia, slope stability has become one of the most pressing issues in the construction sector. Improper slope analysis design can result in slope collapse, which is one of the most common disasters that can result in significant property and lives loss. To deal with these problems, a slope failure analysis must be performed to establish the slope stability by performing limit equilibrium method. Besides, geosynthetics installation has been made to improve the ground stabilization and soil reinforcement. This method will display factor of safety for any particular slope embankment and retaining wall. This research investigates slope stability and offers a ground enhancement strategy that is both cost-effective and safe to use on the slope which is by using Fibrogrid-geogrid as reinforcing elements. The slope stability analysis will be done by using numerical analysis in physical based modelling software, GeoStudio-SLOPE/W. Similar case to previous research, limit equilibrium method is being used to analyze factor of safety but under different circumstances such as slope stability of the highway under rainfall condition and slope stability of a road fill embankment. Besides, Mohr-Coulomb model criteria is also being used to represent the soil layer. In this study, two other hypothesis can be made which are the usage of geosynthetics will give the high impact on safety index for all slope characteristic and increment of surcharge loading that distributed on top of the structure will address to failure if the load capacity is exceeding the ability of reinforced structure by analyzing its factor of safety. This slope failure research has contributed to local engineering research addressing the slope collapse that occurred in three different case studies. The findings of this study can be used as a guide for engineers to improve the slope stability of retaining walls and embankments at these three locations, as well as any other slope in the future.